2005
DOI: 10.1177/1097184x05277716
|View full text |Cite
|
Sign up to set email alerts
|

Text, Body, and Tools

Abstract: This article explores processes by which masculinities change, using examples from the Norwegian forestry industry. Forestry has traditionally been one of the most masculine rural work activities and an arena where hegemonic rural masculinity is expressed. The study is based on mediations of masculinity in a forestry magazine covering a period of twenty years. Using text, body, and tools as an analytic scheme, pictures of temporal variations of, and relations between, "traditional" and "new" types of masculini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Networks for women were initially formed as a response to exclusionary practices in Swedish forestry, and they should be understood as a strategy by which to resist the subordination of hegemonic femininity in forestry. The interviewees clearly articulated their experience of Swedish forestry as a male space in which (hegemonic) masculinity is normative, which is in line with the findings from other studies on forestry (e.g., Lidestav 2016, Brandth andHaugen 2005;Johansson et al 2019a;Johansson, Johansson, and Andersson et al 2018;Lidestav and Egan Sj€ olander 2007;Reed 2003). Many interviewees brought up examples of exclusion in both symbolic and material forest spaces, i.e., exclusion from the idea of the forest as a male space, as well as exclusion in forest courses and activities, representation in forest owner associations, and from the use of material items such as forest gear and protective clothing (because of the sizes and designs being based on the male body).…”
Section: Negotiating Femininities and Challenging Hegemonic Masculinisupporting
confidence: 85%
See 3 more Smart Citations
“…Networks for women were initially formed as a response to exclusionary practices in Swedish forestry, and they should be understood as a strategy by which to resist the subordination of hegemonic femininity in forestry. The interviewees clearly articulated their experience of Swedish forestry as a male space in which (hegemonic) masculinity is normative, which is in line with the findings from other studies on forestry (e.g., Lidestav 2016, Brandth andHaugen 2005;Johansson et al 2019a;Johansson, Johansson, and Andersson et al 2018;Lidestav and Egan Sj€ olander 2007;Reed 2003). Many interviewees brought up examples of exclusion in both symbolic and material forest spaces, i.e., exclusion from the idea of the forest as a male space, as well as exclusion in forest courses and activities, representation in forest owner associations, and from the use of material items such as forest gear and protective clothing (because of the sizes and designs being based on the male body).…”
Section: Negotiating Femininities and Challenging Hegemonic Masculinisupporting
confidence: 85%
“…the urban powerful organizational masculinity does not influence the rural tough masculinity. In contrast to Stenbacka's (2011) finding that rural masculinities are subordinated to urban masculinities Brandth and Haugen (2005) argued that the rural tough forestry worker represents hegemonic masculinity in relation to the urban powerful organizational man, as they found that in the rural setting of their study, practical experiencebased knowledge was valued higher than white-collar managerial expertise. This result is in line with the findings of Lidestav and Egan Sj€ olander (2007), who, based on a discourse analysis of forestry profession advertisements, argued that the ideal forester is continually reproduced 'as a hard-working and nature-mastering man' (351).…”
Section: Masculinities Femininities and Ruralitymentioning
confidence: 57%
See 2 more Smart Citations
“…The changing nature of discourses of work and gender is revealed in a study of the Norwegian Forest Owner's Federation newsletter, The Forest Owner undertaken by Brandth and Haugen (1998;2005a;2005b). The authors undertake an exploration of gendered representations of farming at four historical moments from the 1970s to the present.…”
Section: Gender Discourse and Employmentmentioning
confidence: 99%